Healthcare Professionals and Patient Perceptions on the Use of Herbal Medicines to Control Diabetes Mellitus and Hypertension in Nigeria - Nwankwo Ogechukwu Lucy; Ogbonna Brian Onyebuchi (CV. Literasi Indonesia, 2023)
The perception that herbal medicines are generally safe and non-toxic, has all necessitated patients' use of herbs in the management of diabetes and hypertension. The study evaluated healthcare professionals' and patients' perceptions of the use of herbs to control diabetes mellitus (DM) and hypertension. The study utilized a randomized sampling method for the survey; an online form was designed and used for data collection. The questionnaire was sent to professional and non-professional groups having the target population (patients and relatives. The results showed that the majority of the participants stated the use of Vernonia amagdalena in the management of HTN (33.0%) and DM (9.9%). Other plants mentioned include Moringa leaves HTN n (5.5%), DM n(6.6%); Carica papaya; HTN (9.9%), DM (8.2); Ginger, and DM (12.6%). Dogoyaro/Agbo (4.9%). Notable antidiabetic plants reported in this study include Rauwolfia vomitoria (1.1%), Ugu leaves (2.2%), Hibiscus (zobo) (4.4%), Ocimum gratiscimum (1.1%), cucumber (1.1%), neem plant (3.8%). Previous knowledge on Diabetes Mellitus between the patients and healthcare workers was P=0.038 while previous knowledge on hypertension was p=0.029. The knowledge of herbal product(s) used in diabetes was p=0.043 while knowledge of herbal product(s) used in hypertension was p=0.019, at p<0.05. It was thus concluded that the participants believe that herbal medicines can relieve disease within a short period, are effective at the correct dosage, have fewer side effects or no side effects at the proper doses, and can effect a complete cure if standardized, affordable, better tolerated in the body.